Developing 21st Century Competencies of Marginalized Students Through the Use of Augmented Reality (AR) (LEARNing Landscapes, 2018)
In this article, we share an ethnographic case study of how we worked with a small group of marginalized grades 6, 7, and 8 students to both explore and create augmented reality (AR) to produce a class cookbook. We discuss how using AR helped students develop digital literacies skills and 21st century competencies, while at the same time, integrating AR into the students’ life skills component of their programming helped them also develop cooking skills and basic nutrition awareness. The findings suggest that AR has great potential in educational contexts and can be used in cross-disciplinary ways that go beyond STEM-focused programming.
Keywords: augmented reality; digital literacies; 21st century competencies